Qualitative data for examining fixed and incremental concepts of language learning: A search for the stories behind students’ motivation - Burns, Laura V. Fielden; García, Mercedes Rico (Universitas Pendidikan Indonesia, 2018)
Although quantitative tools are often employed to examine students’ beliefs in language learning, qualitative interviews can offer further depth and insight on these beliefs, by shedding light on the detail of the experiences behind student perceptions. This is important to understanding student motivation in the language classroom, since beliefs form one of the important pillars behind motivation and language learning goals. The present study analyzed beliefs for 8 students in English for Hospitality vocational courses (2 male and 6 female from 25 to 43 years of age) in one-to-one, narrative interviews, looking both to the content of what students chose to share and the form in which they expressed themselves. This population is particularly interesting given that other studies in vocational studies indicate a lack of study persistence due to problems in motivation. Utilizing this qualitative, open-ended approach allowed the authors to more specifically examine how students conceive language learning when understood as a story of their experience with languages. The rich descriptions that emerge from this methodology have been imported for future curriculum planning, as they describe in more detail students’ tendencies to categorize language learning as something passive or active, as an object or as a process, which should be taken into account in course planning to optimize study persistence.